[PP.36.22]: IS HYPERTENSION A RISK FACTOR FOR NEW ONSET ATRIAL FIBRILATION IN PATIENTS WITH ACUTE CORONARY SYNDROME?. (June 2015) - Boskovic>, A.>; Vukmirovic, M.; Nikolic, G.; Ratkovic, M.; Vujosevic, S.; Medenica, M.
Abstract : Objective: New-onset atrial fibrillation (AF) is a common complication of acute coronary syndrome (ACS). The aim of the study was to evaluate the incidence of AF in patients with ACS and to evaluate if arterial hypertension is a risk factor for new-onset AF in patients with ACS. Design and method: We included 600 patients with ACS, 290 with STEMI and 310 with NSTEMI. At entry, all patients were in sinus rhythm. The AF group included patients with ACS and new onset AF and control group included patients with ACS without AF during the hospital course. Results: Mean age of patients was 63.6 ± 10.6 years, between them 425 were men and 275 women, mean BMI was 26.8 ± 2.6 kg/m2. The incidence of new-onset AF was 8% in the patients with ACS during hospital course. In AF group there were 48 patients and in control group were 552 patients. We analyzed risk factors for coronary artery disease (CAD) and incidence of AF and found that the patients in AF group were older 69.9 ± 9.4 years versus 63.1 ± 11.4 in control group and with higher BMI (28.0 ± 2.6 kg/m2 in AF group versus 26.7 ± 2.6 kg/m2 in control group), p < 0.01. In AF group there were 26 patients (54.2%) with hypertension versus 268 (48.6%) in the control group, p > 0.05. There was also not difference in gender distribution, frequency of smokers, diabetes mellitus and family history for CAD between the groups, p > 0.05. Multivariable logistic regression analyses showed that from risk factors for CAD older age, OR (95% CI) is 2.37 (1.23–4.58), p = 0.01 and increased BMI, OR (95% CI) is 1.17 (1.04–1.33), p = 0.012 were independent predictors of new onset AF in the patients with ACS. Conclusions: The incidence of new-onset AF was 8% in the patients with ACS during hospital course, but hypertension was not significant risk factor for new onset AF. The independent predictors of new-onset AF from risk factors for CAD in the patients with ACS were older age and increased BMI.